The role of a political blog: the case of www.commentary.co.za - Kathy Goldfain; Nadia van der Merwe (Communicare)
With the inception of new technologies and the Internet, media users can consult a variety of diverse sources for their daily news. The latest innovations to have an impact on the traditional news landscape are weblogs, commonly referred to as blogs. Blogs have become a significant new way to publish information and engage in conversation about social and political issues. This paper explores the role of the political blog, www.commentary.co.za, as a news medium as perceived by selected Johannesburg bloggers. Through qualitative research, the respondents concurred that while a news blog will probably never replace traditional media, it can be used effectively to promote the exchange of information and offer new perspectives on issues. In addition to this, they believe that blogs can be a form of participatory journalism and complement journalism.